AKTIFITAS ANTIBAKTERI EKSTRAK SIRIH MERAH DAN LIDAH MERTUA TERHADAP BAKTERI ESCHERICHIA COLI - Irene Puspa Dewi; Verawaty Verawaty; Tuty Taslim; Rusvaira Khairunnisa (Jurnal Katalisator, 2020)
Based on previous studies note that the red betel leaf and lidah mertua leaf has a pharmacological activity as an antibacterial against Escherichia coli. This research aims to compare the antibacterial activity between ethanol extract of red betel leaf and lidah mertua leafÂ  againts bacterium Escherichia coli. The research used the agar diffusion method to measure the diameter of the inhibition area formed around the paper disc. Each extract ethanol is prepared with a concentration of 10% and 20%. As a positive control used ciprofloxacin. The result shown that inhibition area diameter of ethanol extract of red betel leaf with a concentration 10% is 0,97cm and 20% is 1.23 cm. Inhibition area diameter of ethanol extract of lidah mertua leaf with a concentration 10% is 1.20 cm and 20% is 1.53 cm. One Way Anova statistical analysis concluded that the average of inhibition area diameter between the ethanol extract of red betel leaf and lidah mertua leaf did not differ significantly both at concentrations of 10% and 20%. From these results we concluded that there was no significant difference in antibacterial activity of ethanol extract of red betel leaf and lidah mertua leaf againts the bacterium Escherichia coli.